AN ANALYSIS OF GRAMMATICAL ERRORS MADE BY THE THIRD YEAR STUDENTS OF SMAN 1 PEKANBARU IN WRITING RECOUNT TEXTS - Fadhil Akbar; Eliwarti Eliwarti; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to know the grammatical errors made by the third years of SMAN 1 Pekanbaru the academic year 2018/2019 in writing recount text. Descriptive method was employed in this research with both qualitative and quantitative approaches. The selected sample was XII MIA 5 students which consisted of 28 students. The sample was selected by using random sampling technique. The research findings provided the most common types of errors made by the students was error of selection with the number of errors was 323 or 78,00%. Moreover, it was followed by error of omission with the number of errors was 48 or 11,60%, and errors in addition and ordering fewer than 6%. Error of additon with the number of errors was 24 or 5,80% errors and errors of misordering with the number of errors was 19 or 4.60%. The errors performed by the students of SMA 1 Pekanbaru were caused by the influence of the first language and the second languageKeywords: Error Analysis, SMAN 1 Pekanbaru, Omission, Addition, Misordering, Selection.